Pendampingan Pembelajaran dengan Metode Game Based Learning untuk Meningkatkan Ilmu Pengetahuan Agama Islam di TPQ Al Barokah Dusun Malangsari - Amir Mukminin; Mujahidin (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2022)
TPQ is one of the means of Islamic da'wah in which it is taught about reading and writing the Qur'an and the basic teachings of Islam. TPQ Al Barokah is one of the TPQ located in Malangsari Hamlet, Bulusulur. The number of students at TPQ Al Barokah is approximately 12 people and each student is gifted with their own uniqueness and character. There are children who like to seek attention by throwing tantrums and are difficult to manage, but there are also those who are diligent and obedient to the teacher, paying attention when explained the learning material. The author in his service at TPQ Al Barokah uses a game-based learning method. This service aims to create a learning atmosphere that is fun, full of enthusiasm, relaxed but serious and is expected to stimulate and foster the creativity and knowledge of students about the science of Islam. The result of this service is that students at TPQ Al Barokah are very enthusiastic in participating in the game. There are some students who previously when explained by the lecture method they did not pay attention and ran here and there after this game the child wanted to pay attention and follow the game until it was finished.